Design, fabrication and testing of a power operated paddy dibbler - Jayarajan R (Department of Farm Power Machinery and Energy, Kelappaji College of Agricultural Engineering and Technology, 1996)
A 2-row power operated paddy dibbler was designed, fabricated and tested at Kelapaji College of Agricultural Engineering and Technology, Thavanur. The main components of the dibbler were two seed boxes, plungers reciprocating within the seed tubes, fluted roller seed metering mechanism, dibbler wheels, stationary cam, frame and transport wheels. The seed tubes were fixed radially around the dibbler wheel with 45 mm of it projecting outwards for penetrating the soil. The plunger was actuated by a stationary cam and during its upward stroke it uncovered the farther end of the seed transfer tube and transferred the seeds into the seed tube and then into the holes made in the soil. In the downward stroke the plunger closed the seed transfer tube. Simultaneously the fluted roller transferred the seeds in to the seed transfer tube. The average speed of operation of the dibbler was 1.32 kmph and its field capacity and field efficiency were 0.031 ha/h and 78.18 per cent respectively. The average number of seeds dropped per hill was 5 and the seed rate obtained was 78 kg/ha. The seeds were placed within the confines of the holes made by the seed tube and plunger. There was absolutely no scattering. The depth of placement varied from 3.8 to 4.6 cm. The operating cost of the dibbler was Rs. 502.58/ha. This mechanism offers scope for developing dibblers with more number of rows for being operated more economically.